IMPLEMENTASI MANAJEMEN RESIKO TERHADAP PEMAKSIMALAN NILAI KEUANGAN PERUSAHAAN - Fatihatul Ishlahiyah, Siti; Ni’mati Rahmatika, Arivatu (LPPM Universitas KH. A. Wahab Hasbullah, 2019)
Abstract: Objectives - The objective of this research is to implement risk management on financial value. In this study using qualitative methods. This study aims to determine the implementation of risk management to maximize the financial value of the company. Based on this research, it shows that there are ways to identify company risk management, the importance of company value, and financial management tasks, one of which is to maximize company finances. Keywoards: Risk management, corporate value, financial management